Neuroinflammation in epileptogenesis: from pathophysiology to therapeutic strategies - Li, Wenjun; Wu, Jinze; Zeng, Yini; Zheng, Wen (Frontiers in Immunology, 2023)
Epilepsy is a group of enduring neurological disorder characterized by spontaneous and recurrent seizures with heterogeneous etiology, clinical expression, severity, and prognosis. Growing body of research investigates that epileptic seizures are originated from neuronal synchronized and excessive electrical activity. However, the underlying molecular mechanisms of epileptogenesis have not yet been fully elucidated and 30% of epileptic patients still are resistant to the currently available pharmacological treatments with recurrent seizures throughout life. Over the past two decades years accumulated evidences provide strong support to the hypothesis that neuroinflammation, including microglia and astrocytes activation, a cascade of inflammatory mediator releasing, and peripheral immune cells infiltration from blood into brain, is associated with epileptogenesis. Meanwhile, an increasing body of preclinical researches reveal that the anti-inflammatory therapeutics targeting crucial inflammatory components are effective and promising in the treatment of epilepsy. The aim of the present study is to highlight the current understanding of the potential neuroinflammatory mechanisms in epileptogenesis and the potential therapeutic targets against epileptic seizures.